Financial Literacy, Digital Payments, and Saving Behavior of Gen Z - Aminuddin Hamdat; Ramlah Ramlah; Izaac L D Lawalata; Muhammad Rizal; Andi Lutfi (LP2M IBK Nitro, 2026)
This study examines the influence of digital financial literacy and digital payments usage on saving behavior among Generation Z. In the digital era, financial transactions have increasingly shifted toward cashless systems, raising concerns about how digital financial environments shape financial decision-making and saving habits among young individuals. Using a quantitative approach, data were collected from 186 Generation Z respondents who actively use digital payment services. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and moderating relationships among variables. The results indicate that digital financial literacy has a positive and significant effect on saving behavior. Digital payments usage also shows a positive influence on saving behavior. Furthermore, digital financial literacy significantly strengthens the relationship between digital payments usage and saving behavior, suggesting that financially literate individuals are better able to utilize digital payment platforms to support financial discipline rather than impulsive spending. These findings highlight the importance of integrating digital financial literacy into financial education programs to ensure that increased access to digital financial services contributes to improved financial resilience among Generation Z. The study provides practical implications for policymakers, educators, and financial institutions in promoting sustainable financial behavior in the digital economy